2012
DOI: 10.4028/www.scientific.net/msf.729.216
|View full text |Cite
|
Sign up to set email alerts
|

Development of PA6/HDPE Nanocomposite Blends

Abstract: In our experiments polyamide 6/high density polyethylene blends (25/75 wt%) were produced and maleic anhydride grafted polyethylene was used as chemical coupling agent. To get finer microstructure and enhance the mechanical properties the blends were compounded by different nanostructured reinforcements. Two kinds of nanosilicate, the layered structure montmorillonite and the needle like sepiolite were applied in different concentrations and their effect on the mechanical and melting properties were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Various research groups prepared polymer blends and reinforcing materials filled polymer blends. 8 10 Scaffaro et al 11 prepared polyamide 6/high density polyethylene/clay nanocomposites and showed that the incorporation of nanoclay into polymer blends improve the mechanical properties. The polymer blend system can be used for preparation of polymer electrolyte by the addition of liquid electrolyte to polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups prepared polymer blends and reinforcing materials filled polymer blends. 8 10 Scaffaro et al 11 prepared polyamide 6/high density polyethylene/clay nanocomposites and showed that the incorporation of nanoclay into polymer blends improve the mechanical properties. The polymer blend system can be used for preparation of polymer electrolyte by the addition of liquid electrolyte to polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…New components in blends with other polymers can improve the performance. PLA composites take less impact on the environment compared to other polymers like PA6/HDPE nanocomposites [15]. Studies show that for PLA materials Reactive Extrusion (REX) modified thermoplastic starch particles can be used as bio-based and biodegradable nucleating agent to increase the rate and percent of crystallization, an also improve oxygen barrier properties [16].…”
Section: Literature Review and Analysis Of Possible Materialsmentioning
confidence: 99%
“…Nowadays, nanocomposites have opened a new way in the development of polymer blends and composites. Thus, the tensile strength and Young's modulus can be further increased by using nanoclay like montmorillonite [5].…”
Section: Introductionmentioning
confidence: 99%